Gambaran BMI (Body Mass Index) Pasien Kanker Nasofaring Yang Menjalani Terapi IMRT di Unit Radioterapi RSUP Prof. Dr. I.G.N.G Ngoerah - Serly Olivia Natalia Dato; I Made Lana Prasetya; Retno Laksmi Faraningrum (An-Najat, 2023)
One of the cancers that causes the highest mortality is nasopharyngeal cancer. The number of nasopharyngeal cancer cases in Indonesia reached 19,943 new cases with a mortality rate of 13,399. Radiotherapy is the main treatment modality and part of standard care for cancer patients. The way radiotherapy works is to damage the DNA chain of tumor cells in order to kill tumor cells directly and eliminate the ability to proliferate. Giving radiation to the head and neck region has an influence on weight loss. The purpose of this study was to describe the BMI (Body Mass Index) of nasopharyngeal cancer patients who underwent IMRT therapy at the Radiotherapy Unit of Prof. Dr. I.G.N.G Ngoerah Hospital. The type of research used is quantitative research with an observational approach using retrospective data. The samples of this study were 25 patients with nasopharyngeal cancer who underwent IMRT therapy from January to December 2021 at the Radiotherapy Unit of Prof. Dr. I.G.N.G Ngoerah Hospital. The results of this study showed 25 samples of nasopharyngeal cancer patients who underwent IMRT therapy experienced weight loss with an average of 13.01 and BMI with an average of 4.93. Based on the results of the Statistical Test which shows that the p value <0.05 which means there is a decrease in body weight in nasopharyngeal cancer patients undergoing IMRT therapy in the Radiotherapy Unit of Prof. Dr. I.G.N.G Ngoerah Hospital. Of the 25 samples of nasopharyngeal cancer patients who underwent IMRT therapy, there were changes in BMI (Body Mass Index) before irradiation and after irradiation. This is evident from the normality test value and Paired Twhich shows a p value <0.05, meaning that there is a decrease in body weight in nasopharyngeal cancer patients undergoing IMRT therapy.